Case Report: Role of hypoglycemia in seizure aggravation in a case of focal epilepsy: revealing a missing link between diabetes and dementia - Ohara, Hiroya; Yamanaka, Masami; Inoue, Kiyoko; Shimizu, Hironori; Iguchi, Naohiko; Tanaka, Keiko; Gopalakrishnan, Abilash Valsala; Vellingiri, Balachandar; Kinoshita, Masako (Frontiers in Neuroscience, 2025)
AimWhile low-frequency electroencephalographic (EEG) activity increases during hypoglycemia, the relationship between hypoglycemia and changes in epileptic activities has not been fully investigated. Recently, the American Clinical Neurophysiology Society’s EEG Terminology 2021 defined criteria for Brief Potentially Ictal Rhythmic Discharges (BIRDs) including rhythmic fast activities. We evaluated the association between hypoglycemia and BIRDs.MethodsData from a 27-year-old female with focal epilepsy and idiopathic hypoglycemia, who underwent scalp-recorded long-term video-EEG using the International 10—20 system with T1/T2 electrodes, were analyzed. Her anti-neuronal antibody test results were negative. EEG recordings over 6 h were retrospectively evaluated in longitudinal bipolar montages at 15 s per display screen. The number and duration of BIRDs were assessed in each 30 min epoch. Glucose levels were obtained using a flash glucose monitoring system, and the average glucose level for each epoch was calculated using the area under the curve (AUC), measured by pixel-counting software. The relationship between the number and duration of BIRD subtypes and average glucose levels was evaluated using cut-off values of 70, 60, and 50 mg/dL.ResultsDuring the recording, the EEG showed focal slow activities, epileptic spikes, and BIRDs in the left temporal area, but no clinical or electrographic seizures were observed. The number of evolving BIRDs per epoch was significantly higher during more severe hypoglycemia when the cut-off values were set at 60 mg/dL (2.00 ± 0.71 vs. 0.38 ± 0.70, mean ± SD, p < 0.05, Mann–Whitney U test) and 50 mg/dL (2.33 ± 0.47 vs. 0.44 ± 0.68, p < 0.05). The total duration of definite BIRDs per epoch also showed a statistically significant difference when the cut-off was set at 50 mg/dL (3.15 ± 1.82 vs. 2.10 ± 1.00 s, p < 0.05).ConclusionMaintaining glucose levels above 60 mg/dL appears important for the early termination of epileptic rhythmic discharges. Individuals with diabetes are at high risk of Alzheimer’s disease (AD), and hippocampal hyperactivity contributes to epileptic seizures, amyloid deposition, and disease progression. Fluctuations in blood glucose levels, including episodes of hypoglycemia, increase the risk of dementia. The present findings suggest a potential causative role of hypoglycemia in AD and propose a precise method to correlate glucose levels with brain activities.